Socialization and Training on the Use of Straw as Fertilizer and Fuel (BRICKETS) to Increase Benefits in Indah Sari Village, Mekar Sari District (Barito Kuala) - Risnawati; Rina (Jurnal Pengabdian Pancasila (JPP), 2023)
Agricultural waste is generally in the form of straw which after the harvest season is simply thrown away so that if this is done continuously it will be wasteful and will not produce any other benefits. However, agricultural waste can be processed into more useful things such as fertilizer and fuel (briquettes). In the community service outreach here, efforts are being made to provide knowledge and training regarding the processing of straw waste as natural fertilizer and alternative fuel in the form of briquettes so that it can provide more benefits to the community. The target audience is 30 PKK women from Indah Sari Village, Mekarsari District, Barito Kuala Regency. The results of this community service are an increase in understanding and knowledge of PKK women in Indah Sari Village regarding the benefits of straw waste, outreach and training activities can solve the problem of PKK women in Indah Sari Village regarding agricultural waste, PKK women in Indah Sari Village know how to process straw waste into fertilizer and briquettes.